Optimal design of a muffler for reliable noise attenuation in case of uncertainty of noise source - Lee, Jong Kyeom; Lee, Jin Woo (INTER-NOISE 2018 - 47th International Congress and Exposition on Noise Control Engineering: Impact of Noise Control Engineering, 2018)
This paper suggests a design method for reliable noise attenuation of a muffler independent of changeable operating condition of noise source. Two uncertainties due to operate condition are considered. One is the temperature of noise, and the other is the dominant frequency of noise source. To the end, a reliability-based acoustical topology optimization problem is formulated for a simple expansion chamber muffler. A finite element model is used for acoustical analysis and reliability analysis. In the reliability-based acoustical topology optimization problem, one design variable is assigned to each element and determines the acoustic properties of an associated finite element. The design variable changes continuously between 0 and 1. When the design variable becomes 1, the associated finite element is filled with a rigid body element. The rigid body elements forms partitions. The partition volume is selected as an objective function, and the reliability of noise attenuation performance due to uncertainties is constrained. The formulated optimization problem is solved for a given design condition by using gradient-based optimizer, MMA (Method of moving asymptotes). Finally, the obtained optimal result is compared with the result obtained without considering uncertainties.
Keywords: Acoustical analysis; Dominant frequency; Expansion chamber; Method of moving asymptotes; Noise attenuation; Objective functions; Operating condition; Optimization problems